Analysis of Local Wisdom Integration in Biology Learning to Support Education for Sustainable Development (ESD) - Zebua, Nofamataro; Malik, Padmaning Fathimah Pudya (Universitas Cokroaminoto Palopo, 2025)
This study analyzes the integration of local wisdom in biology learning as an effort to support Education for Sustainable Development (ESD). Local wisdom includes various knowledge and practices that contribute to environmental sustainability and play a role in enriching biology learning to make it more contextual and meaningful. The results showed that the application of local wisdom, such as traditional practices in natural resource management and the utilization of medicinal plants, can help students understand the concepts of ecosystems, biodiversity and conservation better. In addition, this approach is aligned with ESD goals, including improving the quality of education, sustainable consumption and production, and mitigating climate change. Nevertheless, the implementation of local wisdom in learning still faces obstacles, such as limited teaching materials and the readiness of educators. Therefore, supportive policies, training for teachers, and development of local wisdom-based learning media are needed to achieve ESD goals optimally.